Financing without Bank Loans New Alternatives for Funding SMEs in China - Wang, Jiazhuo G.; Yang, Juan (Springer Nature Singapore : Imprint: Springer, 2016)
This book covers all important financial innovations for SME financing, and combines theoretical analysis and real world practices employed in China's financial market. As China is increasingly becoming a key player in the global economy, the book helps readers gain a better understanding of the current structure and operation of, as well as future changes in, the Chinese economy. Given the high likelihood of RMB joining the IMF's SDR in the near future, this book offers a well-timed publication that will prove valuable for a broad readership, either as a reference book or as a guide to understanding, researching, teaching on and making business decisions about China and related issues.